Financial dependence and intimate partner violence (IPV) among married Syrian refugee women living in non-camp settings in Jordan - Ajita Singh; Nabila El-Bassel; Neeraj Kaushal; Melissa Meinhart; Jennifer Komos Hartmann; Trena Mukherjee; Maysa' Khadra; Ruba Jaber; Raeda Al-Qutob; Anindita Dasgupta (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Globally, several studies show that the prevalence of intimate partner violence (IPV) is associated with the financial dependence of women on their husbands. Limited research exists on the relationship between IPV and male partner financial dependence among refugees, especially Syrian refuge women in host countries. This paper is designed to examine the relationship between financial dependence of Syrian refugee women on their husbands in the host country and IPV perpetrated by husbands. We hypothesize that women whose financial dependence on their husbands increased in the host country Jordan as a result of displacement caused the Syrian Civil War are more likely to report experiences of IPV within the past 12 months as compared to women whose financial dependence on their husbands did not increase or change. # Methods We recruited 507 Syrian refugee women for the project Advancing Solutions in Policy, Implementation, Research and Engagement for Refugees (ASPIRE) study using time and venue-based random sampling from health clinics in Jordan in 2018. Eligibility criteria included: being a female Syrian refugee, living in non-camp settings, and being at least 18 years of age. Women participated in face to face interviews on gendered health and mental health concerns, physical and sexual IPV in the past year, and financial dependence on their husbands. In this paper we focused on women who were married prior to the Syrian civil war (N=313). We asked if the war in Syrian increased, decreased, or did not change the financial dependence on the husband. We used multivariable logistic regression to examine the association between financial dependence and IPV, adjusting for covariates of age, education, family decision-maker in the household, marital status, number of children in the household, and Syrian governorate prior to leaving Syria. # Results On average, women were 35.7 (standard deviation, SD=9.05) years. Nearly half (41.2%) reported a decrease in financial dependence on their husbands after the Syrian civil war. A little over one-fifth (20.5%) of the women reported an increase in financial dependence on their husbands after the Syrian civil war. More than one-third (38.3%) of Syrian refugee women in the study reported that their financial dependence on their husbands did not change. Nearly two-fifths of women (38.7%) reported experiencing IPV in the past 12 months. Participants who experienced a decrease in financial dependence had 1.99 higher odds (adjusted odds ratio, aOR=1.99, 95% CI, confidence interval=1.11-3.58) of experiencing IPV in the past 12 months. Participants who experienced an increase in financial dependence also had 1.96 higher odds (aOR=1.96, 95% CI=1.00-3.81) of experiencing IPV in the past 12 months. Therefore, we found that women whose financial dependence on their husbands either increased or decreased were both more likely to report experiencing IPV perpetrated by husbands in the last 12 months, suggesting the possible implications of disrupted stability in a relationship in conflict situations, compared to women whose financial dependence on their husbands did not change after the Syrian civil war. # Conclusions IPV prevention efforts in changing household dynamics among Syrian refugee married couples should be considered while developing potential economic empowerment intervention programs. As women may be more likely disclose their financial dependence changes than IPV experiences, these lessons could benefit the health and humanitarian sector in identifying women's health and protection needs.